DERIVATIONAL ADAPTATION OF ENGLISH LOAN WORDS INTO THE ADJECTIVE SUBSYSTEM OF THE UKRAINIAN LANGUAGE - Bytkivska, Ya. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article tackles the issue of the behavior of English loan-words (adjectives) in the derivational system of the Ukrainian language. It particularly covers the issue of their adaptation to the word-building norms of the target language, collocations with domestic lexemes, as well as the influence of foreign elements upon the microstructures of the target language. The practical material consists of the anglicisms used in mass media, fiction, conversational speech and internet resources. The terms “direct anglicism” (English lexemes borrowed from the source language by means of transcription or/and transliteration) and “mediated anglicism” (borrowed English lexemes that on the ground of the target language obtained new word-buildings and form-building affixes) are introduced. According to the research that social orders as well as the popularity of some anglicisms accelerate their adaptation to the word-building peculiarities of the Ukrainian language. After the attachment of the derivative formants the mediated anglicisms widen their denotation range by means of new semes. The modification suffixes emphasize the subjective attitude of a speaker towards the nomination object. Transpositional and mutative suffixes cause the expansion of word-building nests. The widespread usage of anglicisms in everyday speech and slang caused their adjustment to phonetic games and linguistic experiments. On the other hand, the utilizations of suffixoids as well as word-building substantive structures show the influence of the source language on the target one.